Exploring cardiovascular and respiratory fitness: A comparative study of adolescents involved in extracurricular activities - Zubaida, Ida; Ruhiat, Yayat; Hendrayana, Aan; Anugrah, Sendy Mohamad (UIR Press, 2024)
Background Problems: The critical importance of maintaining physical fitness among high school students to mitigate the potential health hazards associated with a sedentary lifestyle. Research Objectives: This study aims to explore the impact of futsal and hadang extracurricular activities on adolescent cardiovascular and respiratory fitness. Methods: This research used an experimental study with pre-post design and control group. Ninety students from Serang City high schools were divided into three groups: Futsal Extracurricular, Hadang Extracurricular, and Control. Initial assessments established baseline fitness levels, followed by an 8-weeks program and post-program evaluations. Findings and Results: The results showed an increase in aerobic capacity and respiratory capacity after 8-weeks extracurricular program in both groups. The futsal extracurricular group experienced a higly significant increase aerobic capacity and respiratory capacity compared to the baseline. Meanwhile, the hadang extracurricular group experienced a significant increase aerobic capacity and respiratory capacity compared to the baseline. Conversely, the control group appears to exhibit a decline in both aerobic and respiratory capacities, although it is important to note that these changes did not reach statistical significance in our study. Conclusion: In conclusion, this study provided valuable insights into how futsal and hadang extracurricular activities impact adolescent cardiovascular and respiratory fitness. These findings were relevant for educators and policymakers, highlighting the role of extracurricular programs in enhancing students' overall well-being. Additionally, it contributes to our understanding of how specific activities can influence the cardiovascular and respiratory health of adolescents.